Behavioral Intention of Domestic Organic Waste Segregation in Urban Communities (Case Study: Sukmajaya and Cilodong Districts, Depok City) - Putri, Rohana Carolyne; Karuniasa, Mahawan; Wahyono, Sri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Waste management is a significant and widespread issue that challenges many countries, particularly developing countries. Organic waste is a primary contributor to greenhouse gas (GHG) emissions in waste management, making it a crucial problem to address. Proper waste management practices, including decentralized organic waste management, are necessary to address this issue. However, this decentralization requires the support of the community’s waste segregation behavior. Therefore, this study was conducted in Sukmajaya and Cilodong Districts to analyze the intention of organic waste sorting behavior utilizing Theory of Planned Behavior (TPB) analysis. The results showed that only two constructs, attitude and perceived behavioral control, positively impacted the intention to sort organic waste. In this study, norm construction does not serve as a supporting construction for the waste sorting intention. Additionally, knowledge of waste sorting programs and activities significantly affects perceived behavioral control.